The Influence Of Organizational Culture And Job Satisfaction Towards The Performance Of Pt Torabika Eka Semesta Employees - Angel Limbong; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti International Journal of Digital Business Management, 2026)
The aim of the research is to describe and analyze the significant influence of organizational culture on employee performance, the significant influence of job satisfaction on employee performance and analyze the influence of organizational culture and job satisfaction on employee performance, This research uses a quantitative approach, descriptive and associative type. There is an influence of organizational culture on employee performance in the organization , as evidenced by the calculated t value for the Organizational Culture variable (X1 ) of 7.425 while the t table value for n = 66 is 1.996 . So 7.425 > 1.996 , then H0 is rejected and Ha is accepted , There is The influence of job satisfaction on employee performance in the organization , is proven by the calculated t value for the Job Satisfaction variable (X2 ) of 9.625 , while the t table value for n = 66 is 1.996 . So 9.625 > 1.996 , then H0 is rejected and Ha is accepted . There is an influence of organizational culture and job satisfaction on employee performance . It is proven from the ANOVA test or calculated F value obtained by the calculated F of 2.85 , 298 , while the F table ( 0.05) for n = 66 is 2.74 . So the calculated F > from the F table ( 0.05 ) or 2.85 , 298 > 2.7 4 with a significance level of 0.000 because 0.000 < 0.05, it can be said that Organizational Culture (X 1 ) and Job Satisfaction (X 2 ) together or simultaneously have a positive effect on Employee Performance (Y)